Plant-Microbe Interactions in Phytoremediation - (:unkn) unknown (Elsevier Inc., 2015)
Our atmosphere, water resources and soil are becoming increasingly contaminated with inorganic and organic compounds as a result of anthropogenic-driven inputs, mainly from industry, mining, motorized traffic, agriculture, logging and military actions. Alleviation and prevention of environmental pollution can be achieved by utilization of plants and their associated microbes. Recent advances in plant-microbe interaction research revealed that plants are able to shape their rhizosphere microbiome through active secretion of substrates that are known to vary between plant species. Soil-borne microorganisms such as actinobacteria, algae, protozoa and different types of bacteria having different capabilities of functional activities can vary extensively in soils and occur in associations in the rhizosphere of plants. Microbial associations are known to affect mobility and availability of substances to the plant through the release of chelating agents, acidification, phosphate solubilization and redox changes and exudates derived from the plant can help to stimulate the survival and action of these microorganisms. A broad knowledge about the mechanisms in plants for the uptake, translocation, storage, and detoxification of contaminants, and interactions between plants and microorganisms are critical in developing technologies and best management practices for environmental clean-up. A comprehensive understanding of interactions between plants and rhizospheric microorganisms in the rhizosphere and plant-based processes will provide new opportunities to develop more efficient plants and better management practices for removal of contaminants. This chapter reviews plant-microbe interactions in phytoremediation with particular reference to the microbial dynamics in the rhizosphere of plants growing on contaminated soils. © 2015 Elsevier Inc. All rights reserved.
Keywords: Environmental clean-up; Hyperaccumulator; Microbiome; Plant-microbe interactions; Rhizosphere